PENGARUH PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN AKTIVITAS PENGENDALIAN TERHADAP AKUNTABILITAS KEUANGAN: STUDI PADA SKPD KABUPATEN/KOTA PROPINSI BANTEN - Nurhayati Soleha (Faculty of Economic and Business, 2014)
The aim of this research is to analyze the effect of implementation of regional financial accounting system and control activities on financial accountability. The method used in this research is explanatory survey method. The analysis method that used in this research is path analysis. The result of the analysis shown that the implementation of regional financial accounting system and control activities give positive and significant influence simultaneously reaches 55,20% on financial accountability. The second result shown the implementation of regional financial accounting system give positive and significant influence reaches 20,05% on financial accountability. The third result shown the implementation of control activities give positive and significant influence reaches 35,15% on financial accountabilityDOI: 10.15408/etk.v13i1.1876